2015
DOI: 10.1556/2006.4.2015.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparing problem gamblers with moderate-risk gamblers in a sample of university students

Abstract: Background and AimsIn an effort to provide further empirical evidence of meaningful differences, this study explores, in a student population, the distinctions in gambling behavioral patterns and specific associated problems of two levels of gambling severity by comparing problem gamblers (PG) and moderate-risk gamblers (MR) as defined by the score on the Problem Gambling Severity Index (PGSI; MR: 3-7; PG: 8 and more).MethodsThe study sample included 2,139 undergraduate students (male = 800, mean age = 22.6) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Women spend less on on‐line gambling than men . High gambling expenditure is associated clearly with problem gambling , as is high gambling frequency and increased experienced harms . Many aspects of women's and men's gambling behaviour appear to differ considerably .…”
Section: Introductionmentioning
confidence: 99%
“…Women spend less on on‐line gambling than men . High gambling expenditure is associated clearly with problem gambling , as is high gambling frequency and increased experienced harms . Many aspects of women's and men's gambling behaviour appear to differ considerably .…”
Section: Introductionmentioning
confidence: 99%
“…Although the latter procedure is understandable from a methodological perspective, as, particularly in representative surveys, the number of pathological gamblers is often too small for statistical analysis, it is nevertheless questionable when it comes to content. Thus, Shen et al ( 2015 ) showed that moderate-risk gamblers (Problem Gambling Severity Index (PGSI): 3–7) differ significantly from problem gamblers (PGSI: ≥8) regarding psychological distress and possible alcohol dependence. Furthermore, the latter group participates significantly more frequently in poker games and sports betting and also takes part in online gambling considerably more often.…”
Section: Introductionmentioning
confidence: 99%
“…The final interview sample constituted of seven MR and all (n = 5) of the PG. Although significant differences can be found between MR and PG (Shen et al, 2015), both groups were combined to have a sufficient number of cases for category saturation during analysis. Both focus group discussions and individual interviews gathered information on gambling context (e.g., gambling location and setting, gambling partners) and practices (e.g., expenditures and time, subjective experiences).…”
Section: Methods Sampling and Data Collectionmentioning
confidence: 99%
“…Although average gambling expenditures increase across the gambling spectrum from non-problem to problem gambler groups, problem gamblers were found to spend at least $250 per month compared to $41.6 for moderate-risk gamblers, and 7.05% of annual income compared to 1.51% in each respective groups (Currie, Hodgins, & Casey, 2013). Within university populations, analyses of monthly spending and annual debt have also revealed that problem gamblers spend significantly more money and accumulate significantly more annual debt than moderate-risk gamblers (Shen, Kairouz, Nadeau, & Robillard, 2015). College students have been known to present more risky behaviours, including a greater vulnerability to gambling problems (Powell, Hardoon, Derevensky, & Gupta, 1999).…”
Section: Introductionmentioning
confidence: 99%